Analisis Keterampilan Proses Sains Mahasiswa pada Praktikum Biologi Lingkungan Materi Bioindikator Pencemaran Air - Dian Putri Utami; Ima Aryani (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to understand skills in the science process in the environmental biology practicum on water pollution bioindicator material. This research method is a qualitative research method that involves descriptive analysis. The research results show that the order of indicator percentages from largest to smallest is, a) observations of 89%; b) classification of 87%; c) interpretation of 86%; d) communication of 83%; e) prediction of 78%; f) asking questions of 76%; g) hypothesizing of 69%; h) using tools and materials of 67%; i) applying the concept of 66%; j) planning an experiment of 63%. The conclusion of this research is that all PPP indicators appear in practicum. Keywords: Biology, KPS, Practicum